REDESIGN LOGO PADEK.CO - BASRI KHAIRUNNAS, Dr. Budiwirman, M.Pd., Henra Afriwan, S.Sn., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
One of the companies engaged in digital media is Padang Ekspres Digital Media, or commonly known as Padek.co. Padek.co is a news and e-paper portal company from West Sumatra which was established in 2014 which can be accessed via multiplaform such as websites, mobile apps on Android and IOS. Since its inception Padek.co already has a logo, but the logo does not function well in the promotion process that is carried out, as a result the promotional media that is designed is not consistent so that Padek.co does not yet have a characteristic of its visual identity. Efforts to redesign the Padek.co logo are needed to keep this company in the position of consumers.The method used in this design is SWOT analysis by finding strength, weakness, oppurtunity and threat. Begins with the interview stage with the founder and observation to the Padek.co office to collect the data needed in this design process.The design produces the main media in the form of a logo that is designed in a manual book or a logo guide. The main media will be equipped with supporting media including manual books, business cards, mugs, pins, t-shirts, posters, x-banners, stickers and hats.Keywords: padek.co, redesign, logo, positioning.